Dictionary of Pharmaceutical Medicine - Nahler, Gerhard (Springer Vienna : Imprint: Springer, 2009)
In the beginning was the word - and the foreword. Words are c- bined to sentences and eventually language. Words are listed in a dictionary and their meaning in building language are explained in a lexicon. In the life sciences - e. g. drug development sciences and pharmaceutical medicine - the analogies are evidenced by the - nomic library and patho-physiological function as the lexicon. In this transition from code to function integrated lexica pay a pivotal role for a faster understanding. The present updated version of this books combines dictionary and lexicon and provides the translational - derstanding of the complex drug development process. With a large number of new terms, their abbreviations and explanations in this complex interdisciplinary process a great number of different dis- plines and specialists need to be informed: they include physicians, pharmacists, biologists, chemists, biostatisticians, data managers, - formation specialists, business developers, marketing experts as well as regulators, financing specialists, healthcare providers and ins- ers in a continuous professional development mode. This lexicon is therefore a most suitable and economical tool for fast and conclusive information for all key-players in the development of medicines at the working place, in postgraduate training as well as during graduate education. This book is an indispensible aid in any medical library. Prof. Dr. med. Dr. h. c. Fritz R.